Resistant Hypertension after Hypertensive Intracerebral Hemorrhage Is Associated with More Medical Interventions and Longer Hospital Stays without Affecting Outcome - Hong, Daojun; Stradling, Dana; Dastur, Cyrus K.; Akbari, Yama; Groysman, Leonid; Al-Khoury, Lama; Chen, Jefferson; Small, Steven L.; Yu, Wengui (Frontiers in Neurology, 2017)
Background: Hypertension (HTN) is the most common cause of spontaneous intracerebral hemorrhage (ICH). The aim of this study is to investigate the role of resistant HTN in patients with ICH. Methods and Results: We conducted a retrospective study of all consecutive ICH admissions at our medical center from November 2013 to October 2015. The clinical features of patients with resistant HTN (requiring 4 or more antihypertensive agents to keep systolic blood pressure < 140 mm Hg) were compared with those with responsive HTN (requiring 3 or fewer agents). Of the 152 patients with hypertensive ICH, 48 (31.6%) had resistant HTN. Resistant HTN was independently associated with higher body mass index and proteinuria. Compared to the responsive group, patients with resistant HTN had higher initial blood pressures and greater requirement for ventilator support, hematoma evacuation, hypertonic saline therapy, and nicardipine infusion. Resistant HTN increases length of stay (LOS) in the intensive care unit (ICU) [4.2 vs 2.1 days; p= 0.007] and in the hospital (11.5 vs 7.0 days; p= 0.003). Multivariate regression analysis showed that the rate of SBP >140 mm Hg and duration of nicardipine infusion were independently associated with LOS in the ICU. There was no significant difference in hematoma expansion and functional outcome at hospital discharge between the two groups. Conclusions: Resistant HTN in patients with ICH is associated with more medical interventions and longer LOS without effecting outcome at hospital discharge.